The Influence of Economic Status on the Reading Preferences of Nigerian Primary Pupils - Lasisi, Monica; Adeyanju, ‘Lade (2014)
Conclusive evidence that socio-economic status, among other factors, affects the book choices of young readers has so far eluded reading comprehension researchers. Thus, the quest still goes on for a statistically valid instrument that may be used as a measure of reading preferences. Through such investigation, an accurate reading interest scale might be provided. Accordingly, the present study sets out to determine the effect of social status on the book selections of children while employing a non-verbal test instrument in the form of pictures.